Visual search strategies of children with and without autism spectrum disorders during an embedded figures task - Horlin, Chiara; Albrecht, Matthew; Falkmer, Marita; Leung, Denise; Ordqvist, Anna; Tan, Tele; Lee, Wee; Falkmer, Torbjorn (Elsevier Inc., 2014)
Individuals with ASD often demonstrate superior performance on embedded figures tasks (EFTs). We investigated visual scanning behaviour in children with ASD during an EFT in an attempt replicating a previous study examining differences in visual search behaviour. Twenty-three children with, and 31 children without an ASD were shown 16 items from the Figure-Ground subtest of the TVPS-3 while wearing an eye tracker. Children with ASD exhibited fewer fixations, and less time per fixation, on the target figure. Accuracy was similar between the two groups. There were no other noteworthy differences between children with and without ASD. Differences in visual scanning patterns in the presence of typical behavioural performance suggest that any purported differences in processing style may not be detrimental to cognitive performance and further refinement of the current methodology may lead to support for a purported advantageous cognitive style.